Dependence of Information Entropy of Uniform Fermi Systems on Correlations and Thermal Effects - Moustakidis, Ch. C.; Massen, S. E. (HNPS Advances in Nuclear Physics, 2020)
The influence of correlations of uniform Fermi systems (nuclear matter, electron gas and liquid 3He) on Shannon’s information entropy, S, is studied. It is found that, for three different Fermi systems with different particle interactions, the correlated part of S (Soor) depends on the correlation parameter of the systems or on the discontinuity gap of the momentum distribution through two parameter expressions. The values of the parameters characterize the strength of the correlations. A two parameter expression also holds between Scor and the mean kinetic energy (K) of the Fermi system. The study of thermal effects on the uncorrelated electron gas leads to a relation between the thermal part of S (Sthermai) and the fundamental quantities of temperature, thermodynamical entropy and the mean kinetic energy. It is found that, in the case of low temperature limit, the expression connecting Sthermai with Κ is the same to the one which connects Scor with K. Thus, regardless of the reason (correlations or thermal) that changes K, S takes almost the same value.